Measurement of Portal Pressure and its Application in the Clinical Setting - Pierce, Jonathan D.; Esparaz, Anthony M.; Malik, Raza (Digestive Disease Interventions, 2017)
Portal hypertension is a severe, yet common sequela of patients with chronic liver disease and is responsible for many of the complications seen in this population. Measurement of the hepatic venous pressure gradient (HVPG) is the current gold standard technique for identifying and evaluating the severity of portal hypertension. Any increase in HVPG to ≥10 mm Hg is considered clinically significant portal hypertension. Above this threshold, complications of portal hypertension begin to manifest. In addition to assessing portal hypertension, various HVPG thresholds have been shown to have strong prognostic value for risk of complications and therapeutic failure, as well as survival in patients with chronic liver disease. These clinical applications include quantification of disease progression and regression in chronic viral hepatitis, acute alcoholic hepatitis, and hepatocellular carcinoma. Other applications include preoperative evaluation of liver resection and transplantation in patients with cirrhosis and hepatocellular carcinoma, assessment of response to therapy for portal hypertension, and identification of the need for transjugular intrahepatic portosystemic shunt (TIPS) revision.
Keywords: portal hypertension; hepatic venous pressure gradient; variceal hemorrhage; portal pressure; cirrhosis